The Influence Of Managerial Ownership And Firm Size On Firm Value In Manufacturing Companies Listed On The Indonesia Stock Exchange For The Period 2019–2023 - Lukmanul Hakim; Husnul Khotimah; Ghea B. Astrid Sunanto (Asosiasi Dosen Muda Indonesia, 2025)
This study explores the influence of managerial ownership and firm size on firm value among manufacturing companies listed on the Indonesia Stock Exchange. The research adopts a quantitative approach by utilizing secondary data derived from annual financial statements published over a span of several years. Managerial ownership is represented by the proportion of shares held by managers, directors, and commissioners, while firm size is measured using the natural logarithm of total assets. Firm value is assessed through the Tobin’s Q ratio, which reflects market perception of a firm’s performance and growth potential. The panel data regression analysis is employed using a structured model selection process, including fixed effect and random effect model evaluations. The findings reveal that both managerial ownership and firm size positively and significantly influence firm value. These results highlight the strategic importance of aligning internal ownership structures and scaling firm operations to enhance corporate value and attract investor confidence